PERILAKU PHUBBING REMAJA PEMAIN GAME PLAYER UNKNOWN’S BATTLE GROUND (PUBG) MOBILE DI KOTA DENPASAR - Bagus Wicaksono, R. Agung Rezky; Pradipta, Ade Devia; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
ABSTRACT The purpose of this research is to explain the teenagers phubbing behavior in PUBG mobile game players in Denpasar City. This study uses a qualitative approach and uses the theory of media dependency, where this theory states that the more a person depends on a medium to meet their needs, the more important the media becomes for that person and uses Behavioral Cognitive theory. Behavioral Theory wants to analyze only behaviors that are visible, measurable, described and predictable and Cognitive Theory states that humans do not react passively to the environment, but as living beings who always try to understand their environment using the "SR" (stimulus - response) model describes the information process between "stimulus" (stimulus) and "response" (response). The results of this study indicate that a person performs phubbing behavior while playing the Game Player Unknown Battle Ground (PUBG) Mobile with a different form of behavior for each individual. Keywords: New Media, Player Unknown's Battle Ground, Phubbing, Media Dependency, Behavioral and Cognitive .